A new quality of teaching solfeggio in the system of music education - Gulnar T. Alpeisova, Gulzada N. Omarova, Raushan S. Maldybayeva, (Opción, 2019)
The article is devoted to practical aspects of solfeggio musicians training according to the new methods in the framework of the discipline Ethnic solfeggio through content analysis of contextual features related to identity structure in the works of others. Analysis of modern methods of teaching solfeggio shows that further development of this discipline goes beyond its classical definition and has a number of peculiarities in various countries. In conclusion, with the help of a training course ethnic solfeggio, the musicians returned the ability to improvise and composition activity, the ability to combine the motives of traditional music with the modern